Sensitivity Test of Herbal Extracts of Jarem Grass (Grona triflora), Meniran (Phyllanthus niruri), and Patikan Kebo (Euphorbia hirta) Against Terrestrial Bacteria - Nufus, Lale Syifaun; Ifada, Andy Susbandiyah; Radiah, Nur; Pahmi, Khairil (International Journal of Health and Information System, 2024)
Sensitivity is the ability of a medicinal substance to kill or inhibit the growth of microbes. Meanwhile, intermediate is a condition where there is a shift from a sensitive state to a completely resistant state. Method research was experimental and several procedural processes were  sterilization, making of MHA media, bacterial cultivation, and extract preparation. Result showed that the highest diameter of the inhibition zone for the extract was found in the Grona triflora extract in group 1, which was 35 mm and followed by Phyllanthus niruri extract in group 6 which was 29 mm. Furthermore, the inhibition zone diameter of positive control, ciprofloxacin and tetracyclines, were 40 mm. The active ingredients of Grona triflora are flavonoids, alkoloids, and phenolics and the components of meniran that are  flavonoid and tannin compounds are estimated as the inhibition factor that cause the inhibition zone in the media. Finally, the inhibitory zone of grass jarem herb extract (Grona triflora) (EGT) and  the inhibitory zone for extract of Phyllantus niruri  (EPN) are called to have the similar level of sensitivity when compared with several types of antibiotics ciproploxacin and tetracycline which have the sensitive level ≥ 21 mm.